2011
DOI: 10.1186/1471-2288-11-117
|View full text |Cite
|
Sign up to set email alerts
|

Questions asked and answered in pilot and feasibility randomized controlled trials

Abstract: BackgroundIn the last decade several authors have reviewed the features of pilot and feasibility studies and advised on the issues that should be addressed within them. We extend this literature by examining published pilot/feasibility trials that incorporate random allocation, examining their stated objectives, results presented and conclusions drawn, and comparing drug and non-drug trials.MethodsA search of EMBASE and MEDLINE databases for 2000 to 2009 revealed 3652 papers that met our search criteria. A ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
198
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(208 citation statements)
references
References 64 publications
1
198
0
2
Order By: Relevance
“…In evaluating the feasibility trial and its methods, several of the methodological issues identified by Shanyinde 50 have been addressed elsewhere. Chapter 4 has addressed the quantitative findings in relation to sample, eligibility, recruitment, consent, randomisation and outcomes; Chapter 5 has addressed some aspects of adherence and fidelity to the PCAM intervention; and Chapters 3 and 6 have explored the acceptability of the PCAM intervention.…”
Section: Field Note Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In evaluating the feasibility trial and its methods, several of the methodological issues identified by Shanyinde 50 have been addressed elsewhere. Chapter 4 has addressed the quantitative findings in relation to sample, eligibility, recruitment, consent, randomisation and outcomes; Chapter 5 has addressed some aspects of adherence and fidelity to the PCAM intervention; and Chapters 3 and 6 have explored the acceptability of the PCAM intervention.…”
Section: Field Note Analysismentioning
confidence: 99%
“…This included assessing whether or not recruitment, retention and data collection were achieved to a sufficient level, and whether or not the outcomes used were sensitive enough to detect change (at what level and for whom), as well as identifying any key methodological issues in converting from a feasibility or pilot trial to a full-scale trial, as established by Shanyinde et al 50 We used a tool known as 'A process for Decision-making after Pilot and feasibility Trials' (ADePT). 51 The ways in which researchers decide to respond to the results of feasibility work may have significant repercussions for both the nature and degree of tension between internal and external validity in a definitive trial.…”
Section: Integration and Synthesis Of Data Setsmentioning
confidence: 99%
“…Feasibility and pilot studies are not expected to have the large sample sizes that are needed to adequately power statistical null hypothesis testing. Indeed, pilot studies that are published often do not show statistically significant findings and rarely lead to larger trials to adequately power the hypothesis testing (Arain et al, 2010;Shanyinde et al, 2011). The outcomes of most feasibility and pilot studies should be measured with descriptive statistics, qualitative analysis, and the compilation of basic data related to administrative and physical infrastructure.…”
Section: Distinguishing Feasibility and Pilot Studiesmentioning
confidence: 99%
“…(Research Methods section,para. 6) Although the literature on feasibility and pilot study designs is relatively new and is not consistent with respect to these definitions, the emerging methodological literature suggests that both feasibility and pilot studies should be addressed specifically to descriptively assessing the feasibility and validity of the RCT plan and not to testing the hypotheses of the main RCT (Arain, Campbell, Cooper, & Lancaster, 2010;Leon, Davis, & Kraemer, 2011;Shanyinde, Pickering, & Weatherall, 2011;Thabane et al, 2010). Feasibility and pilot studies are not expected to have the large sample sizes that are needed to adequately power statistical null hypothesis testing.…”
Section: Distinguishing Feasibility and Pilot Studiesmentioning
confidence: 99%
“…2,4 However, the terms used for these preliminary studies are sometimes considered synonymous, 13 and in practice may overlap considerably or be combined. 11,13 The important issue is not the distinction between these: the important distinction is between such preliminary studies and a proper RCT (TABLE).…”
mentioning
confidence: 99%